How Job Crafting Dimensions Differentially Moderate the Translation of Work Conditions into Stress Perceptions - Giovanni Di Stefano; Elena Lo Piccolo; Lavinia Cicero (Behavioral Sciences, 2025)
Job crafting—employees’ proactive modification of their work—has gained attention as a potential stress management strategy. This study examined how job crafting dimensions moderate relationships between work conditions and stress perceptions. Integrating Effort–Reward Imbalance and Job Demands–Resources models, we tested whether three job crafting dimensions (increasing structural resources, social resources, and challenging demands) moderate the translation of factual work conditions into stress perceptions. Survey data from 376 Italian employees revealed that factual effort and reward indicators positively predicted their perceived counterparts. Contrary to expectations, increasing structural resources amplified rather than buffered the effort perception relationship, suggesting that certain crafting strategies may heighten rather than reduce awareness of work demands. As hypothesized, increasing social resources buffered the effort relationship and strengthened the reward relationship. Increasing challenging demands showed no significant moderating effects. These findings reveal that job crafting dimensions have differential rather than uniformly positive effects on stress perception processes. While social crafting appears consistently beneficial, structural crafting may have unintended consequences under certain conditions. Organizations should recognize that job crafting interventions require nuanced implementation. The study advances theory by demonstrating boundary conditions for job crafting effectiveness and challenging assumptions about its uniformly positive effects.